An observer blinded, randomized, placebo-controlled, phase I dose escalation trial to evaluate the safety and immunogenicity of an inactivated West Nile virus Vaccine, HydroVax-001, in healthy adults. Issue 30 (9th July 2019) - Woods, Christopher W.; Sanchez, Ana M.; Swamy, Geeta K.; McClain, Micah T.; Harrington, Lynn; Freeman, Debra; Poore, Elizabeth A.; Slifka, Dawn K.; Poer DeRaad, Danae E.; Amanna, Ian J.; Slifka, Mark K.; Cai, Shu; et al.
Abstract: Background: West Nile virus (WNV) is the most common mosquito-borne infection in the United States. HydroVax-001 WNV is a hydrogen peroxide inactivated, whole virion (WNV-Kunjin strain) vaccine adjuvanted with aluminum hydroxide. Methods: We performed a phase 1, randomized, placebo-controlled, double-blind (within dosing group), dose escalation clinical trial of the HydroVax-001 WNV vaccine administered via intramuscular injection. This trial evaluated 1 mcg and 4 mcg dosages of HydroVax-001 WNV vaccine given intramuscularly on day 1 and day 29 in healthy adults. The two dosing groups of HydroVax-001 were enrolled sequentially and each group consisted of 20 individuals who received HydroVax-001 and 5 who received placebo. Safety was assessed at all study days (days 1, 2, 4 and 15 post dose 1, and days 1, 2, 4, 15, 29, 57, 180 and 365 post dose 2), and reactogenicity was assessed for 14 days after administration of each dose. Immunogenicity was measured by WNV-specific plaque reduction neutralization tests (PRNT50 ) in the presence or absence of added complement or by WNV-specific enzyme-linked immunosorbent assays (ELISA). Results: HydroVax-001 was safe and well-tolerated as there were no serious adverse events or concerning safety signals. At the 1 mcg dose, HydroVax-001 was not immunogenic by PRNT50 but elicited up to 41% seroconversion by WNV-specific ELISA in the per-protocol population (PP) after the second dose. At the 4 mcg dose, HydroVax-001 elicited neutralizing antibody responses in 31% of the PP following the second dose. In the presence of added complement, PRNT50 seroconversion rates increased to 50%, and 75% seroconversion was observed by WNV-specific ELISA. Conclusions: The HydroVax-001 WNV vaccine was found to be modestly immunogenic and well-tolerated at all dose levels.